A systematic review of outcome reporting in clinical trials of distal tibia and ankle fractures: the need for a core outcome set. (3rd October 2022) - Pearson, Nathan A.; Tutton, Elizabeth; Joeris, Alexander; Gwilym, Stephen E.; Grant, Richard; Keene, David J.; Haywood, Kirstie L.
Abstract : Aims: To describe outcome reporting variation and trends in non-pharmacological randomized clinical trials (RCTs) of distal tibia and/or ankle fractures. Methods: Five electronic databases and three clinical trial registries were searched (January 2000 to February 2022). Trials including patients with distal tibia and/or ankle fractures without concomitant injuries were included. One reviewer conducted all searches, screened titles and abstracts, assessed eligibility, and completed data extraction; a random 10% subset were independently assessed and extracted by a second reviewer at each stage. All extracted outcomes were mapped to a modified version of the International Classification of Functioning, Disability and Health framework. The quality of outcome reporting (reproducibility) was assessed. Results: Overall, 105 trials (n = 16 to 669 participants) from 27 countries were included. Trials compared surgical interventions (n = 62), post-surgical management options (n = 17), rehabilitative interventions (n = 14), surgical versus non-surgical interventions (n = 6), and pre-surgical management strategies (n = 5). In total, 888 outcome assessments were reported across seven domains: 263 assessed body structure or function (85.7% of trials), 136 activities (68.6% of trials), 34 participation (23.8% of trials), 159 health-related quality of life (61.9% of trials), 247 processes of care (80% of trials), 21 patient experiences (15.2% of trials), and 28 economic impact (8.6% of trials). From these, 337 discrete outcomes were described. Outcome reporting was inconsistent across trials. The quality of reporting varied widely (reproducibility ranged 4.8% patient experience to 100% complications). Conclusion: Substantial heterogeneity in outcome selection, assessment methods, and reporting quality were described. Despite the large number of outcomes, few are reported across multiple trials. Most outcomes are clinically focused, with little attention to the long-term consequences important to patients. Poor reporting quality reduces confidence in data quality, inhibiting data synthesis by which to inform care decisions. Outcome reporting guidance and standardization, which captures the outcomes that matter to multiple stakeholders, are urgently required. Cite this article: Bone Jt Open 2022;3(10):832–840.